阶级、互动、认同：《幻土》、《爸妈不在家》和《霉运大厦》中新加坡移工的身份建构 = Class, interactions and identity: Singapore migrant workers' construction of self-identity in A Land Imagined, Ilo Ilo and Unlucky Plaza - 郑静琦 Tay, Kimberly Jing Qi (Nanyang Technological University, 2022)
进入全球化时代，移民的涌入对新加坡促进经济繁荣至关重要。虽然移民的经济前景巨大，但移工在试图融入社会时也更易受到歧视和压迫。近年来，不管是关于移工的待遇或政府对移民政策的放宽与紧缩，有关移工的话题都在社会中更受关注。同时，更多以移工为题材的电影也被制作，强调了移工在社会中所面临的负面态度。本文将通过电影《幻土》、《爸妈不在家》和《霉运大厦》中的新加坡移工来探索他们在新加坡的工作与生活经历，讨论他们所面临的挑战和困难，研究他们在本地的阶级、互动与认同如何影响他们的身份建构。本文也会从中提出新加坡潜在的社会问题，并研究移工作为社会孤立与忽略的群体，如何在这个独特的环境中尝试塑造自己的身份认同感。In the era of globalisation, the influx of immigrants is crucial to Singapore’s economic prosperity. While the economic prospects of immigrants are massive, migrant workers are also more vulnerable to facing discrimination and oppression as they attempt to integrate better into society. In recent years, whether it is about the treatment of migrant workers or the government’s immigration policies, the topic of migrant workers has gained much concern in society. At the same time, more films about migrant workers have been produced, emphasising the negative perceptions they face in society. This paper will explore the work and lives of migrant workers in Singapore through the films A Land Imagined, Ilo Ilo and Unlucky Plaza, discuss the challenges and difficulties they face, and examine how their class, interactions and identity will affect their construction of self-identity. This paper will also raise underlying social issues in Singapore and examine how migrant workers, being an isolated and neglected group in society, tries to negotiate their sense of identity in this unique environment.